MULTIKULTURAL PADA ARSITEKTUR MASJID AGUNG PURBOYO DI SIDOARJO - Arsyil Adhiimi (Qurthuba: The Journal of History and Islamic Civilization, 2023)
Abstract: Multiculturalism is the result of a combination of two or more cultural elements that unite and produce a certain cultural result that is somewhat unique (as a result of mixing the two cultures). One of the Islamic religious values that entered and merged into Javanese culture can be seen from the architectural forms of mosques, especially old (ancient) mosques such as the Great Purboyo Mosque which have their own historical value. This article aims to analyze the elements of Islamic and Javanese values in the Purboyo Grand Mosque which can blend and merge very well and have been maintained until today's modern era. This study uses historical methods with an anthropological approach and uses John William Bennet's theory of cultural adaptation as a surgical tool. The results of this study prove that the Great Purboyo Mosque is a historic mosque in Suwaluh Village and has acculturation between Islamic values and Javanese culture which can be seen from the shape of the building (architecture) of the mosque, which is the most prominent form of overlapping terraced roofs (Javanese elements) and calligraphy ornaments. on the gate and part of the mosque wall (Islamic value). Keywords: multiculturalism, Islamic values, Javanese culture, mosque architecture